Marriage as a survival strategy: the case of Masvingo, Zimbabwe - Muzvidziwa, Victor N. (University of Zimbabwe Publications, 2016)
It is the contention of this article that marital hope and pursuit of the marital strategy functions as a survival option for some female heads of households as shown in this study. This article examines how and in what ways female heads of households benefited or were disadvantaged by the lack of or entry into various forms of marital relationships. The experiences of many of the women interviewed for this study showed that the pursuit of the marital strategy had had different outcomes for different individuals at different times. Sometimes, the outcomes were positive, but at other times, the marital strategy had negative results. Through the use of case studies, this article illustrates the outcomes of both losing and gaining 'official husbands', the exploitation of men by 'some tricky' women, and the implications of this behaviour on the development of the family as an institution of socialisation.